Sensemaking Strategies with Immersive Space to Think - Lisle, Lee; Davidson, Kylie; Gitre, Edward J.K.; North, Chris; Bowman, Doug A. (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2021)
The process of sensemaking involves foraging through and extracting information from large sets of documents, and it can be a cognitively intensive task. A recent approach, the Immersive Space to Think (IST), allows analysts to browse, read, mark up documents, and use immersive 3D space to organize and label collections of documents. In this study, we observed seventeen novice analysts perform a historical analysis task in order to understand how users utilize the features of IST to extract meaning from large text-based datasets. We found three different layout strategies they employed to create meaning with the documents we provided. We further found patterns of interaction and organization that can inform future improvements to the IST approach.